Discovery of a chemosynthetic community at a serpentinite-hosted seep on Quaker Seamount, Mariana Forearc - Chong Chen; Hiromi Kayama Watanabe; Jade Castel; Didier Jollivet; François H. Lallier; Margaux Mathieu-Resuge; Loïc N. Michel; Yusuke Motomura; Seitaro Ono; Junichi Miyazaki; Ken Takai (Marine Biodiversity, 2026)

Subtle limits to connectivity revealed by outlier loci within two divergent metapopulations of the deep‐sea hydrothermal gastropod Ifremeria nautilei - Adrien Tran Lu Y; Stéphanie Ruault; Claire Daguin‐Thiébaut; Jade Castel; Nicolas Bierne; Thomas Broquet; Patrick Wincker; Aude Perdereau; Sophie Arnaud‐Haond; Pierre‐Alexandre Gagnaire; Didier Jollivet; Stéphane Hourdez; et al. (Molecular Ecology, 2022)
Hydrothermal vents form archipelagos of ephemeral deep‐sea habitats that raise interesting questions about the evolution and dynamics of the associated endemic fauna, constantly subject to extinction‐recolonization processes. These metal‐rich environments are coveted for the mineral resources they harbour, thus raising recent conservation concerns. The evolutionary fate and demographic resilience of hydrothermal species strongly depend on the degree of connectivity among and within their fragmented metapopulations. In the deep sea, however, assessing connectivity is difficult and usually requires indirect genetic approaches. Improved detection of fine‐scale genetic connectivity is now possible based on genome‐wide screening for genetic differentiation. Here, we explored population connectivity in the hydrothermal vent snail Ifremeria nautilei across its species range encompassing five distinct back‐arc basins in the Southwest Pacific. The global analysis, based on 10,570 single nucleotide polymorphism (SNP) markers derived from double digest restriction‐site associated DNA sequencing (ddRAD‐seq), depicted two semi‐isolated and homogeneous genetic clusters. Demogenetic modeling suggests that these two groups began to diverge about 70,000 generations ago, but continue to exhibit weak and slightly asymmetrical gene flow. Furthermore, a careful analysis of outlier loci showed subtle limitations to connectivity between neighbouring basins within both groups. This finding indicates that migration is not strong enough to totally counterbalance drift or local selection, hence questioning the potential for demographic resilience at this latter geographical scale. These results illustrate the potential of large genomic data sets to understand fine‐scale connectivity patterns in hydrothermal vents and the deep sea.